PEMBUATAN STAND REM CAKRAM PADA MINI TRUCK DENGAN MESIN PENGGERAK DIESEL 5 PK - Pujiono, Akhmad (Universitas Muhammadiyah Pekajangan Pekalongan, 2018)
ABSTRACT The brakes have a very important role in vehicle engineering and transport engineering for security and safety in driving. Brakes are designed to reduce the speed (slow) and stop the vehicle or allow parking on a downhill road. This equipment is very important in a vehicle and serves as a guarantee for the safety and safe driving. Given the importance of the brake as in the description and in connection with the project of making the Mini Truck is done by one of my professors, as well as the material of my thesis, I intend to assist in the manufacture of brake systems (in particular brake discs) on the Mini Truck. Where the disc brakes used are disc brakes on the cars of Honda Accord 1981. . Keywords : Disc Brakes, Making Stand, Mini Truck